Prevalence of Congenital Anomalies in Iran: A Systematic Review and Meta-analysis - Salman Daliri; Kourosh Sayehmiri; Khairollah Asadollahi; Nazanin Rezaei; Diana Saroukhani; arezoo karimi (Mashhad University of Medical Sciences, 2018)
Background: Congenital anomaly is a disturbance in fetal growth and development during pregnancy and is one of the main causes of morbidity and mortality in the first year of life. In addition, this anomaly causes a large waste of heath care resources. We aimed to determine the prevalence and proportion rates of different congenital anomalies in Iran via a systematic review and meta-analysis.Methods: The present study was performed to estimate the prevalence and proportion rates of different anomalies in Iran via a systematic review and meta-analysis. Therefore, all the studies performed in Iran between 2000 and 2016 were evaluated. For this purpose, Medlib, Scopus, Web of Science, PubMed, Cochrane Library, Science Direct, Google Scholar, Irandoc, Magiran, IranMedex, and SID databases were searched by two different expert individuals independently. For the qualification survey of the papers, the Strengthening the Reporting of Observational Studies in Epidemiology checklist was applied. Then, the extracted data were entered into STATA (ver.11.1) and analysed using statistical tests of stability and random effects models in meta-regression, a tool used in meta-analysis. The 95% confidence intervals were calculated by I-square models. Meta regression was introduced to explore the heterogeneities among studies.Results: Overall, 36 papers with a total sample size of 909,961 neonates were analysed. The total prevalence rate for congenital anomalies was 18/1000 live births, 23.2/1000 and 18/1000 for boys and girls, respectively. Moreover, 55.8% of all congenital anomalies pertained to boys. The greatest prevalence and proportion rates of congenital anomalies belonged to musculoskeletal disorders followed by urogenital anomalies (9.3/1000 [34%] and 5.7/1000 [20%], respectively), and the lowest figures belonged to chromosomal and respiratory system anomalies (0.8/1000 [6%] and 0.3/1000 [2%], respectively).Conclusion: According to the findings of this meta-analysis, the prevalence of congenital anomalies is notably high in Iran and annually imposes huge visible and non-visible expenses on individuals, societies, and heath care systems. Therefore, preparation of tools and centres for the early diagnosis and prevention of birth defects and rehabilitation of those with congenital anomalies throughout Iran are essential.